2013
DOI: 10.5539/ass.v9n11p221
|View full text |Cite
|
Sign up to set email alerts
|

Which Organizational Culture Moves towards Organizational Excellency

Abstract: The present research paper studies "the relationship of types of culture and the execution of organizational excellencies based on the EFQM model in government organizations" in which its results are analyzed and interpreted generally. The required data for this research have been collected from 311questionnaires containing questions of personal details and questions about the research hypotheses. In this study, the descriptive statistics methods were used to describe the data such as frequency tables, charts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some studies have focused on the relationship between organizational culture and business excellence, but they have reached different conclusions about whether companies should maintain the existing culture when implementing business excellence or change it and, if so, how (Kekale and Kekale, 1995). The role of organizational culture in achieving business excellence requires more research, and empirical studies should take into consideration that business excellence should be reviewed from a systems perspective (Gogheri et al, 2013).…”
Section: Relationship Between Organizational Excellence and Organizational Culturementioning
confidence: 99%
“…Some studies have focused on the relationship between organizational culture and business excellence, but they have reached different conclusions about whether companies should maintain the existing culture when implementing business excellence or change it and, if so, how (Kekale and Kekale, 1995). The role of organizational culture in achieving business excellence requires more research, and empirical studies should take into consideration that business excellence should be reviewed from a systems perspective (Gogheri et al, 2013).…”
Section: Relationship Between Organizational Excellence and Organizational Culturementioning
confidence: 99%
“…There are also very few studies of companies and organizations that have achieved excellent performance, demonstrated by winning excellence awards (Ahrens, 2013;McAdam et al, 2013). The relationship between organizational culture and business excellence is also a relatively new area for research (Gogheri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It concentrates on the improvement of competitive condition of a company or firm in an industry or a special market. Totally, the business strategy can be competitive (fighting against all competitors for gaining profit) or cooperative (co-operating with one or more competitors to cope with them) or a combination of both (Sadeghi et al, 2013;Jahanshahi et al, 2011d).…”
Section: Literature Reviewmentioning
confidence: 99%